Integrated management of the Blue Nile Basin in Ethiopia: Hydropower and irrigation modeling - Block, Paul J. (International Food Policy Research Institute, 2007)
Ethiopia is at a critical crossroads with a large and increasing population, a depressed national economy, insufficient agricultural production, and a low number of developed energy sources. The upper Blue Nile basin harbors considerable untapped potential for irrigation and hydropower development and expansion. Numerous hydrologic models have been developed to assess hydropower and agricultural irrigation potential within the basin, yet often fail to adequately address critical aspects, including the transient stages of large-scale reservoirs, relevant flow retention policies and associated downstream ramifications, and the implications of stochastic modeling of variable climate and climate change. A hydrologic model with dynamic climate capabilities is constructed to assess these aspects. The model indicates that large-scale development typically produces benefit-cost ratios from 1.2-1.8 under historical climate regimes for the projects specified. Climate change scenarios indicate potential for small benefit-cost increases, but reflect possible significant decreases. Stochastic modeling of scenarios representing a doubling of the historical frequency of El Niño events indicates benefit-cost ratios as low as 1.0 due to a lack of timely water. An evaluation of expected energy growth rates reinforces the need for significant economic planning and the necessity of securing energy trade contracts prior to extensive development. A Ramsey growth model for energy development specifies project multipliers on total GDP over the 100-year simulation ranging from 1.7-5.2, for various climatologic conditions.